The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/eat.23721
|View full text |Cite
|
Sign up to set email alerts
|

Structural validity of the Eating Disorder Examination—Questionnaire: A systematic review

Abstract: Objective: The main aim was to perform a systematic literature review of studies investigating the factor structure of the Eating Disorder Examination-Questionnaire (EDE-Q), a widely used measure of eating pathology. Secondary aims were to summarize the quality of reporting of latent variable (factor) analyses in these studies and review support for different factor solutions.Method: Literature was identified through Scopus, Medline, PsycInfo, and ProQuest databases published up to February 23, 2022 and outrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 86 publications
3
48
1
Order By: Relevance
“…The EDE-Q has been shown to have good internal consistency and other psychometric properties [ 55 ]. Yet, a short version known as the EDE-Q7 [ 56 , 57 ] is described as offering more robust psychometric properties than the original version [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EDE-Q has been shown to have good internal consistency and other psychometric properties [ 55 ]. Yet, a short version known as the EDE-Q7 [ 56 , 57 ] is described as offering more robust psychometric properties than the original version [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in ED pathology may play a central role in lowered recognition and underrepresentation of men in ED research, as standard assessments were developed based on ED presentation in adolescents and young women [ 17 , 18 ]. Consequently, there have already been initial attempts to develop men-specific assessment instruments [ 19 21 ] as well as to validate existing ED assessments in men [ 22 24 ]. For example, the widely used Eating Disorder Examination-Questionnaire (EDE-Q; [ 25 ]), designed to capture the variation and severity in eating-related psychopathology [ 26 ], is based on common cognitive behavioral models of ED.…”
Section: Introductionmentioning
confidence: 99%
“…These and similar findings question the validity of using the EDE-Q subscales for measuring ED pathology in men. Indeed, several studies have shown difficulties reproducing the original EDE-Q factor structure, including in cohorts of men [ 24 , 33 ]. This indicates that the original factor model may not be sensitive to different ED manifestations in adult men [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations